What happens after R1 resection in patients undergoing laparoscopic total mesorectal excision for rectal cancer? A study in 333 consecutive patients. (March 2015) - Debove, C.; Maggiori, L.; Chau, A.; Kanso, F.; Ferron, M.; Panis, Y.
Abstract Aim There are no studies on the respective influence of microscopic involvement at the circumferential (R1c) and the distal margin (R1d) of the surgical specimen on oncological results after laparoscopic mesorectal excision. Method We studied 333 consecutive patients undergoing laparoscopic mesorectal excision for cancer. An R1 resection was defined a by a circumferential and/or distal margin of 1 mm or less. Results Forty (12%) patients had an R1 resection including R1c [n = 28 (70%)], R1d [n = 7 (18%)] or both [n = 5 (12%)]. After a mean of 28 (0–97) months, comparisons of R1 with R0 resection were as follows: mortality 10% and 4% (NS), overall recurrence 48% and 19% (P < 0.001), 2‐year disease‐free survival rate 51% and 76% (P < 0.001) and overall survival (OS) rate 91% and 96% (NS). For R1c patients mortality was 14% (4% for R0; P = 0.026), overall recurrence 46% (19% for R0; P = 0.028) and 2‐year OS 88% (96% for R0; P = 0.025). No significant differences were found between R1d and R0. The metastatic recurrence rate was greater in R1c then R0 (29% vs 12%; P = 0.036) but not for R1d (14% vs 12%; NS). Locoregional recurrence rates of R1c (7%) and R1d (0%) were similar to R0 (4%). Conclusion This study shows that the poorer prognosis observed after R1 resection for rectal cancer is due to circumferential rather than distal involvement. This is mainly related to a higher rate of metastatic recurrence.